How to speak money : the language and knowledge you need now /Ali Velshi, Christine Romans. - Velshi, Ali
Do you speak money? You should. It is the world s most important language. It s spoken everywhere. Speaking--or at least understanding--this language allows you to follow the real conversations in politics, business, and at work. Understanding money and speaking the language fluently is critical to preparing for a comfortable retirement, building a small business, planning for college and a career for your children. Everyone speaks it differently, with different dialects. Some are riskier than others. Some want to save their money; others want to see it grow. There is no one accent, but understanding the differences will make couples, business partners, and coworkers happier--and wealthier. Authors and CNN financial experts Ali Velshi and Christine Romans speak the global language of money and translate it every day for hundreds of thousands of viewers. And they are here to teach you, too. It s easier to learn than you might think. Speaking money affects every area of your life. It s more than simply your savings or the investments you may have. It involves the way you think about money, the way you teach your children about it, and the way you were taught about it yourself. It s about the way you spend it, save it, invest it, use it, need it and want it. The book will: Shed light on the male and female spending and investing disparity Discuss emerging international economies Weigh the financial hurdle of student debt culminating in a successful job Explain how to budget wisely and build wealth Show how to plan appropriately for retirement How to Speak Money is an easy-to-read, practical book that helps readers become fluent in the world s most universal language